(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study assessed the gender and environmental influences on visual function among adults in Owerri, Nigeria. Visual acuity (V.A.) is a measure of visual function in health and disease. Visual disability together with other disabling conditions is a barrier to development, yet there is little known about the visual acuity and determinants of visual function in Owerri, Imo State, Nigeria. Results of a cross-sectional analytical study conducted between September 2007 and November 2009 using 3451 adults living in Owerri, Nigeria consisting of 2606 persons (test) and 845 persons( control), randomly selected are presented. Data were obtained using interviewer administered structured - questionnaires and standard procedures were used to determine gender and environmental influences on visual acuity. There were more females with poor vision than males in both study and control groups. The majority of the subjects were aged 40-49. At 6 metres, 20.9% and 39.1% of study and control groups in the right eye; 31.8% and 41.2% of study control groups respectively in the left eye had unaided V.A. ≥ 6/6. Similarly at 6m, 18.0% and 4.3% of study and control groups in the right eye; 15.2% and 5.0% of study and control groups respectively in the left eye had unaided V.A. < 6/18. Twenty-nine per cent and 25.0% of study and control groups respectively had unaided V.A. at near of N5. Over 70.0% had ≤ N6 at near and V.A. improvement with pin-hole device. Emmetropia was found in 20.5% (study) and 23.2% (control). The percentage prevalence of reduced VA was higher among ametropics and rural dwellers. The contributory factors were poor nutrition & irrational and uncontrolled use of chloroquine as first line drug for malaria treatment. Health education on diet, drug use and safe environmental health practices especially for persons living in rural areas in developing countries are recommended.